Understanding user experience for mobile applications: a systematic literature review - Guoying Lu; Siyuan Qu; Yining Chen (Discover Applied Sciences)
Abstract User experience (UX) has emerged as a critical factor in meeting users’ expectations in mobile application development. However, the existing literature on mobile application user experience (MAUX) fails to offer a comprehensive understanding of key parameters, such as user acceptance, usability, user requirements, feedback, context, and emerging technologies, including augmented reality, virtual reality interactions, and artificial intelligence. To address this gap, this study analyzed 205 documents on MAUX published between 2015 and 2023 from the Web of Science. We developed the Scenarios, Themes, Features, and Methodologies framework to examine both the theoretical and practical applications across multiple dimensions. Our findings reveal that health, learning, and shopping dominate app scenarios with a strong emphasis on personalized UX for diverse populations. Research themes have expanded from usability attributes and user acceptance models to user-centered design processes, exploring how these themes can be fully integrated into MAUX. Interface elements, interaction styles, and performance enhancements are critical design features that influence MAUX across various scenarios. Qualitative, quantitative, and mixed methods are employed flexibly to advance MAUX. Additionally, the integration of complex algorithms has enhanced MAUX’s theoretical framework and methodological approaches. This study underscores the need for a comprehensive and integrated approach to MAUX that considers design, computer science, health, psychology, and other dimensions. It also contributes to a better understanding of the evolving field of MAUX, offering practical insights for researchers, designers, and developers interested in creating more accessible and user-friendly applications(apps) in a rapidly evolving digital landscape.